Is research mediating the relationship between teaching experience and student satisfaction? - Berbegal-Mirabent, Jasmina; Mas-Machuca, Marta; Marimon, Frederic (Studies in higher education (Dorchester-on-Thames), 2018)
Universities must ensure that academic staff are qualified and competent for performing their job. Teaching and research are two key activities in which lecturers should excel. While some authors suggest teaching and research complement each other and positively influence student satisfaction, some others point to a rivalry effect between the two. This study aims at shedding new light on this debate. We first examine the relationship between teaching experience and student satisfaction. In a second stage we explore the mediating effect of research intensity in this relationship. Lastly, we examine potential differences due to contract status. Data gathered in 2014 come from 229 different subjects offered at the Universitat Internacional de Catalunya (Spain). Our results support the thesis that teaching experience is a determinant of student satisfaction. We also found evidence that current incentive systems at universities are research-biased, negatively impacting on students' perceptions of the teaching received (student satisfaction).